Binder suitable for silicon-based negative electrode active material as well as preparation method and application of binder
By using a random copolymer binder obtained by polymerizing acrylic acid and a second monomer in the presence of an organic base in a lithium-ion battery, the current conductive and ion-conducting capabilities of existing binders in silicon-based negative active materials are solved The problem of poor fatigue resistance and poor fatigue resistance has significantly improved the rate performance, cycle performance and capacity of the battery.
Patent Information
- Application Number
- CN202310891734.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
AI Technical Summary
The existing binders have problems such as poor conductivity and ion conductivity and poor fatigue resistance in the application of existing binders in silicon-based negative electrode active materials, which affect the rate performance, cycle performance and capacity performance of lithium-ion batteries.
A random copolymer obtained by polymerizing acrylic acid and a second monomer in the presence of an organic base is used as a binder. This binder effectively inhibits silicone groups by building carboxyl groups on the main chain and branches with sufficient rigidity. The volume of the material changes and the ionic conductivity and dispersion stability are improved by the organic base.
It improves the rate performance, cycle performance and capacity of the battery, enhances the fatigue resistance of the binder, alleviates the volume expansion of the pole pieces during the charge and discharge process, and optimizes the overall performance of the battery.
Smart Images

Figure CN119331547A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a binder suitable for silicon-based negative electrode active materials, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used due to their high energy density, long service life, and low self-discharge rate. Graphite has the advantages of high electronic conductivity, small volume change before and after lithium insertion in a layered structure, and low lithium insertion potential. It has become the mainstream negative electrode active material for lithium-ion batteries. However, the theoretical specific capacity of graphite is 372mAh / g, which limits the improvement of the energy density of lithium-ion batteries. Compared with graphite negative electrode active materials, silicon-based negative electrode active materials have higher specific capacity, but their conductivity is lower, and their volume changes greatly before and after lithium insertion, which can easily lead to problems such as particle pulverization and crushing, electrode structure damage, and battery expansion and bulging, thereby affecting the battery's cycle performance, fast charging performance, and safety performance.
[0003] To solve the above problems, optimization and modification of binders is a cost-effective solution. Binders are a class of polymer compounds with bonding properties. Through their own and the interaction with active materials and current collectors, binders play a key role in maintaining the entire electrode structure in a very small proportion in electrode materials, and also have a certain impact on battery energy density, rate performance, cycle performance and safety.
[0004] The current mainstream binders include PVDF, PAA, CMC\SBR, etc. These binders have shown excellent mechanical and electrochemical properties in existing electrodes, but there are still many limitations in the application of silicon-based negative electrode active materials. Among them, the adhesion between PVDF and CMC / SBR systems and silicon-based materials is insufficient, and they cannot withstand the stress changes generated by silicon-based materials during lithium extraction and insertion; PAA-type materials are relatively excellent binders suitable for silicon-based negative electrode active materials at this stage. Their molecular main chain is relatively rigid, and there are more polar groups on the side chains. They can form tight and dynamic hydrogen bonds with the hydroxyl groups on the surface of silicon materials, which can effectively inhibit the volume change of silicon-based negative electrode active materials. However, the conductivity of PAA binders is low, resulting in high interface impedance, affecting electronic conduction and lithium ion diffusion, and affecting the rate performance and capacity of lithium-ion batteries. In addition, PAA binders have poor fatigue resistance and are easily separated from silicon-based materials after long cycles, resulting in accelerated cycle attenuation and capacity diving of lithium-ion batteries. Summary of the invention
[0005] The present application provides a binder suitable for silicon-based negative electrode active materials to solve the problems of poor electrical and ion conductivity and poor fatigue resistance of PAA binders, thereby improving the rate performance, cycle performance and capacity of batteries.
[0006] The present application also provides a method for preparing the above-mentioned adhesive.
[0007] The present application also provides an electrode sheet, a battery and an electronic device comprising the above-mentioned adhesive.
[0008] In a first aspect, the present application provides a binder suitable for silicon-based negative electrode active materials, wherein the binder is obtained by polymerizing a first monomer and a second monomer in the presence of an organic base;
[0009] The first monomer is acrylic acid;
[0010] The glass transition temperature of the second monomer is not higher than 30°C.
[0011] The binder provided in the present application is a random copolymer obtained by polymerizing a first monomer and a second monomer as polymerization monomers in the presence of an organic base, wherein the first monomer acrylic acid can construct a polymer molecular main chain with sufficient rigidity, providing an effective confinement effect on the volume change of the silicon-based negative electrode active material, and at the same time, the carboxyl group on its side chain can form a tight connection with the hydroxyl group on the surface of the silicon-based negative electrode active material in the form of hydrogen bonds, inhibiting the volume expansion of the silicon-based negative electrode active material during the charge and discharge process, and on the other hand, it also provides sufficient hydrophilicity to improve its dispersion stability in the negative electrode active material layer slurry; the second monomer helps to reduce the glass transition temperature of the polymer molecule with acrylic acid as the main chain, improve the toughness of the polymer molecular chain, and reduce the rigidity of the polymer molecular chain. The possibility of brittle fracture caused by excessive elasticity is reduced, and the ability of the binder to cope with stress fatigue caused by repeated volume changes of silicon-based negative electrode active materials during long cycles is improved, the fatigue resistance of the binder is improved, and the cycle stability of the battery is improved; at the same time, the polymerization process is carried out in the presence of an organic base. On the one hand, the organic base can react with the carboxyl group of acrylic acid to neutralize the binder. The dispersion stability of the binder in the negative electrode active material layer slurry is improved through the action of charge, the bonding performance is optimized, and it is easier to dissociate in the battery to form ion channels, thereby enhancing the ion transmission performance, reducing the interface impedance, and improving the battery's rate performance and capacity. On the other hand, based on the presence of the organic base and the steric hindrance effect, it will affect the polymerization reaction and molecular weight distribution, and affect the processing performance of the battery slurry and the bonding strength of the pole piece.
[0012] In a possible implementation, the content of free carboxyl groups in the binder is not less than 20%.
[0013] By limiting the content of free carboxyl groups in the binder, it is possible to ensure sufficient connection between carboxylic acid groups and hydroxyl groups on the surface of the silicon-based negative electrode active material, and to ensure the dispersibility of the binder in the negative electrode active material layer slurry.
[0014] In a possible implementation, the weight average molecular weight of the binder is 10,000-5,000,000 Da.
[0015] In a possible implementation, the second monomer has a general structural formula of CH2CR1R2, wherein R1 is selected from one or two of H and -CH3, and R2 is selected from -COOC n H 2n ,-COOC n H 2n+1 、-CONH2、-CONH(C n H 2n+1 )、-CON(C n H 2n+1 2. -COOC n H 2n N(C n H 2n+1 ),-COOC n H 2n N(C n H 2n+1 )2, one or more, n = 1 ~ 8.
[0016] In a possible implementation, the second monomer is selected from one or more of methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isooctyl (meth)acrylate, (meth)acrylamide, N,N-dimethylacrylamide, N-methylacrylamide, and dimethylaminoethyl acrylate.
[0017] In a possible implementation, the organic base is selected from one or more of aliphatic amines, aromatic amines, imidazoles, pyridines, pyrroles, piperidines and their derivatives.
[0018] In one possible implementation, the organic base is selected from one or more of methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, aniline, p-phenylenediamine, m-phenylenediamine, 1-ethylimidazole, 4-dimethylaminopyridine, N-methylpiperidine, and 1-methylpyrrolidine.
[0019] In a possible implementation manner, the mass ratio of the first monomer to the second monomer is 1:(0.3-2).
[0020] Controlling the proportion of the first monomer helps to improve the bonding performance, and controlling the proportion of the second monomer helps to improve the flexibility of the electrode. By comprehensively controlling the proportions of the two monomers, an adhesive with better overall performance can be obtained.
[0021] In a possible implementation, the binder is prepared by the following preparation method:
[0022] Dispersing the first monomer, the second monomer and the organic base in a solvent and stirring them uniformly to obtain a mixed solution;
[0023] In an oxygen-free atmosphere, an initiator is added to the mixed solution to carry out a polymerization reaction, and the binder is obtained after the reaction is completed.
[0024] The second aspect of the present application provides a method for preparing any of the above-mentioned adhesives, comprising the following steps:
[0025] Dispersing the first monomer, the second monomer and the organic base in a solvent and stirring them uniformly to obtain a mixed solution;
[0026] In an oxygen-free atmosphere, an initiator is added to the mixed solution to carry out a polymerization reaction, and the binder is obtained after the reaction is completed.
[0027] In a possible implementation manner, the mass ratio of the total mass of the first monomer, the second monomer and the organic base to the solvent is 1:(5-20).
[0028] In a possible implementation, the initiator is azobisisobutyramidine hydrochloride;
[0029] And / or, the mass ratio of the total mass of the first monomer, the second monomer and the organic base to the initiator is 1:(0.001-0.005).
[0030] In a possible implementation, the polymerization reaction is carried out at a temperature of 40° C. to 55° C. for 18 to 24 hours, and the polymerization reaction is carried out under stirring at a stirring speed of 300 rpm to 500 rpm.
[0031] A third aspect of the present application provides an electrode sheet, which includes any of the above-mentioned binders, or includes a binder prepared by any of the above-mentioned preparation methods.
[0032] Based on the binder provided in the first aspect of the present application or the binder prepared by the preparation method provided in the second aspect, the electrode sheet including the binder also helps to improve the rate performance and capacity of the battery.
[0033] In a possible implementation manner, the electrode sheet further includes a cross-linking agent.
[0034] A fourth aspect of the present application provides a secondary battery, comprising any one of the electrode sheets described above.
[0035] Based on the characteristics of the electrode sheet provided by the present invention, a battery including the electrode sheet has good cycle performance, rate performance and capacity utilization.
[0036] A fifth aspect of the present application provides an electronic device, wherein a driving source or an energy storage source of the electronic device comprises any of the secondary batteries described above.
[0037] The electronic device provided in the present application uses the aforementioned secondary battery as a driving source or energy storage unit, so it has excellent battery life and service life.
[0038] The binder provided in the present application is a polymer compound obtained by polymerizing a first monomer, acrylic acid, and a second monomer as polymerization monomers in the presence of an organic base. The binder is suitable for silicon-based negative electrode active materials. The second monomer helps to lower the glass transition temperature of the polymer, improves the toughness of the polymer molecular chain, reduces the possibility of brittle fracture due to excessive rigidity of the molecular chain, and enhances the ability of the polymer molecules to cope with stress fatigue caused by repeated volume changes of silicon-based negative electrode active materials during long cycles, alleviates the volume expansion of the electrode during the charge and discharge process, and improves the cycle stability of the battery; and through the action of the organic base, while optimizing the bonding performance of the negative electrode active material, the ionic conductivity of the binder is improved, the diffusion rate of lithium ions is increased, which is conducive to deep lithium insertion and improves the rate performance and capacity of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the implementation methods in the embodiments of the present application or the related technologies, the following is a brief introduction to the drawings required for use in the embodiments or the related technology descriptions. Obviously, the drawings described below are some embodiments of the present application, and a person skilled in the art can also obtain other drawings based on these drawings.
[0040] Figure 1 The capacity and coulomb efficiency test results of the button batteries provided in Experimental Examples 1-1 to 7-1 and Comparative Example 1-1 of the present application;
[0041] Figure 2 The capacity test results of the button batteries provided in Experimental Examples 1-1 to 7-1 and Comparative Example 1-1 of the present application at different rates. DETAILED DESCRIPTION
[0042] The terms used in the implementation section of this application are only used to explain the specific embodiments of this application and are not intended to limit this application.
[0043] To facilitate understanding, the relevant technical terms involved in the embodiments of the present application are first explained and illustrated.
[0044] Rechargeable battery: also known as rechargeable battery or storage battery, refers to a battery that can be recharged to activate the active material after the battery is discharged and continue to be used.
[0045] Lithium-ion battery: A type of secondary battery that mainly relies on the movement of lithium ions between the positive electrode and the negative electrode to work. During the charge and discharge process, Li+ is embedded and de-embedded between the two electrodes: during charging, Li+ is de-embedded from the positive electrode and embedded in the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; the opposite is true during discharge.
[0046] Positive electrode (cathode): In the primary battery, the electrode from which the current flows has a higher potential and is the positive electrode. It gains electrons for reduction. In the electrolytic cell, the positive electrode is the electrode connected to the positive pole of the power supply and loses electrons for oxidation.
[0047] Anode: The anode is the end of the power source with a lower potential. In a primary cell, it refers to the electrode that performs oxidation, and in an electrolytic cell, it refers to the electrode that performs reduction.
[0048] Electrolyte: The medium that provides ion exchange between the positive and negative electrodes of a battery.
[0049] Battery separator: refers to a layer of separator material between the positive and negative electrodes of the battery. Its main function is to isolate the positive and negative electrodes and prevent electrons in the battery from passing freely, while allowing ions to pass freely between the positive and negative electrodes.
[0050] Conductive agent: ensures that the electrode has good charge and discharge performance, collects microcurrent between active materials and between active materials and current collectors, reduces the contact resistance of the electrode and accelerates the movement rate of electrons, and can also effectively increase the migration rate of lithium ions in the electrode material, thereby improving the charge and discharge efficiency of the electrode.
[0051] Binder: A non-metallic medium material that allows one object to be tightly connected to another.
[0052] Monomer: A general term for small molecules that can polymerize with the same or other molecules. It is a simple compound that can undergo polymerization or condensation reactions to form high molecular weight compounds. It is a low molecular weight raw material used to synthesize polymers.
[0053] Copolymer: A polymerization reaction in which two or more monomers participate together is called copolymerization. The polymer formed contains two or more monomer units. This type of polymer is called a copolymer or interpolymer.
[0054] Random copolymer: The two monomers are randomly arranged on the macromolecular chain and randomly distributed on the main chain. No monomer can form a separate longer chain segment on the molecular chain.
[0055] Organic base: The definition of organic base is relatively broad. Generally speaking, it can be said that organic base is an organic compound containing amino groups in its molecules, such as amine compounds.
[0056] Specific capacity: The amount of electricity that can be discharged by a unit mass of a battery or active material.
[0057] Coulombic efficiency: Under certain charging and discharging conditions, the percentage of charge released during discharge to the charge charged during charging, also called charge and discharge efficiency.
[0058] Binders are non-metallic medium materials that tightly connect one object to another. In battery systems, they are used to tightly connect active materials, conductive agents, and current collectors. Compared with carbon-based negative electrode active materials, silicon-based negative electrode active materials have higher specific capacity, but their electrical conductivity is lower, and their volume changes greatly before and after lithium insertion, which can easily lead to problems such as particle pulverization and crushing, electrode structure destruction, and battery expansion and bulging, thereby affecting the battery's cycle performance, fast charging performance, and safety performance. To solve the above problems, binder optimization and modification is a cost-effective solution. Through the interaction between the binder itself and the active material and the current collector, the binder plays a key role in maintaining the entire electrode structure in a very small proportion in the electrode material, and also has a certain impact on the battery's energy density, rate performance, cycle performance, and safety.
[0059] For example, a Chinese invention patent with publication number CN 103855402 A discloses a negative electrode that can be used for a rechargeable lithium battery, the negative electrode comprising: a current collector; and a negative electrode active material layer, located on the current collector and comprising a negative electrode active material and a binder, wherein the negative electrode active material comprises a silicon-based material, a tin-based material or a combination thereof, the binder comprises an organic acid and an organic base having a cyclic structure, the organic acid comprises a carboxyl-containing polymer. The organic acid comprises at least one selected from polyaspartic acid, alginic acid of a natural polymer, a homopolymer of acrylic acid, a copolymer of acrylic acid and another monomer, and any combination thereof; the organic base is an amine compound having a cyclic structure.
[0060] This patent mainly emphasizes the combination of organic base and organic acid, and does not make specific settings for the structure of organic acid. The introduction of organic base is to neutralize the polar groups of organic acid, which has no effect on the structure of organic acid itself. The overall mechanical properties of the binder and the stability of the electrode slurry largely depend on the selection of organic acid synthesis monomers, which have a large degree of uncertainty.
[0061] A Chinese invention patent with publication number CN 105794029 A discloses a binder for an electrochemical cell, which is formed by a polyolefin copolymer (A), wherein the polyolefin copolymer (A) comprises a structural unit derived from an olefin and a structural unit derived from (meth)acrylic acid, and the carboxylic acid contained in the structural unit derived from the (meth)acrylic acid is neutralized by one or more non-volatile alkaline compounds and one or more volatile alkaline compounds.
[0062] This patent mainly introduces non-volatile alkaline substances to neutralize polyolefin copolymers to reduce the problem of organic solvents contained in their aqueous dispersions. It is not a new binder molecule designed to solve the problem of negative electrode material expansion. The binder molecule it provides is polyethylene-(methyl)acrylic acid copolymer + non-volatile alkaline substance, emphasizing the non-volatility of the alkaline substance without caring whether it can achieve dynamic complexation and decomplexation with the main chain of the binder molecule.
[0063] Based on the above technical problems, the first aspect of the present application provides a binder suitable for silicon-based negative electrode active materials, wherein the binder is obtained by polymerizing a first monomer and a second monomer in the presence of an organic base;
[0064] The first monomer is acrylic acid;
[0065] The glass transition temperature of the second monomer is not higher than 30°C.
[0066] The binder provided in the present application is a random copolymer obtained by polymerizing a first monomer and a second monomer as polymerization monomers in the presence of an organic base, wherein the first monomer acrylic acid can construct a polymer molecular main chain with sufficient rigidity, providing an effective confinement effect on the volume change of the silicon-based negative electrode active material, and at the same time, the carboxyl group on its side chain can form a tight connection with the hydroxyl group on the surface of the silicon-based negative electrode active material in the form of hydrogen bonds, inhibiting the volume expansion of the silicon-based negative electrode active material during the charge and discharge process, and on the other hand, it also provides sufficient hydrophilicity to improve its dispersion stability in the negative electrode active material layer slurry; the second monomer helps to reduce the glass transition temperature of the polymer molecule with acrylic acid as the main chain, improve the toughness of the polymer molecular chain, and reduce the rigidity of the polymer molecular chain. The possibility of brittle fracture caused by excessive elasticity is reduced, and the ability of the binder to cope with stress fatigue caused by repeated volume changes of silicon-based negative electrode active materials during long cycles is improved, the fatigue resistance of the binder is improved, and the cycle stability of the battery is improved; at the same time, the polymerization process is carried out in the presence of an organic base. On the one hand, the organic base can react with the carboxyl group of acrylic acid to neutralize the binder. The dispersion stability of the binder in the negative electrode active material layer slurry is improved through the action of charge, the bonding performance is optimized, and it is easier to dissociate in the battery to form ion channels, thereby enhancing the ion transmission performance, reducing the interface impedance, and improving the battery's rate performance and capacity. On the other hand, based on the presence of the organic base and the steric hindrance effect, it will affect the polymerization reaction and molecular weight distribution, and affect the processing performance of the battery slurry and the bonding strength of the pole piece.
[0067] In one possible implementation, the first monomer is acrylic acid, the second monomer has a double bond group that can participate in the polymerization reaction, and its glass transition temperature is lower than the glass transition temperature of acrylic acid, specifically not higher than 30°C, and the glass transition temperature can be obtained by differential scanning calorimetry (DSC) testing.
[0068] Furthermore, the second monomer has a general structural formula of CH2CR1R2, wherein R1 is selected from one or two of H and -CH3, and R2 is selected from -COOC n H 2n ,-COOC n H 2n+1 、-CONH2、-CONH(CnH 2n+1 )、-CON(CnH 2n+1 2. -COOC n H 2n N(C n H 2n+1 ),-COOC n H 2n N(C n H 2n+1 )2, one or more, n = 1 ~ 8.
[0069] Furthermore, the second monomer is selected from one or more of methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isooctyl (meth)acrylate, (meth)acrylamide, N,N-dimethylacrylamide, N-methylacrylamide, and dimethylaminoethyl acrylate.
[0070] Furthermore, the second monomer is dimethylaminoethyl acrylate, and the end of dimethylaminoethyl acrylate has a polar group, which helps to further improve the bonding performance of the adhesive.
[0071] In a possible implementation, the organic base refers to an organic compound containing an amino group in the molecule, and can be specifically selected from one or more of aliphatic amines, aromatic amines, imidazoles, pyridines, pyrroles, piperidine nitrogen-containing compounds and their derivatives.
[0072] Furthermore, the organic base is selected from one or more of methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, aniline, p-phenylenediamine, m-phenylenediamine, 1-ethylimidazole, 4-dimethylaminopyridine, N-methylpiperidine, and 1-methylpyrrolidine.
[0073] In one possible implementation, the mass ratio of the first monomer to the organic base is 4:1: to 1:1, for example, selected from 4:1, 3.5:1, 3:1, 2.5:1, 2:1, 1.5:1, 1:1 or a range consisting of any two of them; by controlling the mass relationship between the first monomer and the organic base, it is helpful to adjust the pH, viscosity and other properties of the binder, thereby achieving improvement in the slurry processing performance of the binder.
[0074] In one possible implementation, in order to ensure that there are enough carboxylic acid groups connected to the hydroxyl groups on the surface of the silicon-based negative electrode active material and to ensure the dispersibility of the binder in the negative electrode active material layer slurry, the content of free carboxyl groups in the binder is not less than 20%, that is, at least 20% of the carboxyl groups do not undergo neutralization reaction with the organic base.
[0075] In one possible implementation, the mass ratio of the first monomer to the second monomer is 1:(0.3-2), for example, selected from 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2 or a range consisting of any two of them; by controlling the proportion of the first monomer, it helps to improve the bonding performance, and by controlling the proportion of the second monomer, it helps to improve the flexibility of the electrode, and by comprehensively controlling the proportions of the two monomers, a bonding agent with better overall performance can be obtained.
[0076] In a possible implementation, the weight average molecular weight of the binder is 10,000-5,000,000 Da, where the weight average molecular weight refers to the sum of the molecular weight of each molecule multiplied by its weight fraction, and can be obtained by gel permeation chromatography (GPC) testing.
[0077] Furthermore, the weight average molecular weight of the binder is 16000-19000Da.
[0078] In a possible implementation, the binder is prepared by the following preparation method:
[0079] Dispersing the first monomer, the second monomer and the organic base in a solvent and stirring them uniformly to obtain a mixed solution;
[0080] In an oxygen-free atmosphere, an initiator is added to the mixed solution to carry out a polymerization reaction, and the binder is obtained after the reaction is completed.
[0081] In summary, the binder provided in the present application is a polymer compound obtained by polymerization of a first monomer, acrylic acid, and a second monomer in the presence of an organic base as polymerization monomers, and is suitable for silicon-based negative electrode active materials. The second monomer helps to lower the glass transition temperature of the polymer, improves the toughness of the polymer molecular chain, reduces the possibility of brittle fracture due to excessive rigidity of the molecular chain, and enhances the ability of the polymer molecules to cope with stress fatigue caused by repeated volume changes of silicon-based negative electrode active materials during long cycles, alleviates the volume expansion of the electrode during the charge and discharge process, and improves the cycle stability of the battery; and through the action of the organic base, while optimizing the bonding performance of the negative electrode active material, the ionic conductivity of the binder is improved, the diffusion rate of lithium ions is increased, which is beneficial to deep lithium insertion and improves the rate performance and capacity of the battery.
[0082] The second aspect of the present application provides a method for preparing any of the above-mentioned binders, comprising the following steps:
[0083] Dispersing the first monomer, the second monomer and the organic base in a solvent and stirring them uniformly to obtain a mixed solution;
[0084] In an oxygen-free atmosphere, an initiator is added to the mixed solution to carry out a polymerization reaction, and the binder is obtained after the reaction is completed.
[0085] The preparation method of the binder provided in the present application can be obtained by conventional technical means in the art, specifically: a first monomer acrylic acid and a second monomer are selected as polymerization monomers, and a polymer compound is obtained by a polymerization reaction in the presence of an organic base, wherein the addition of the second monomer helps to lower the glass transition temperature of the polymer, improves the toughness of the polymer molecular chain, reduces the possibility of brittle fracture due to excessive rigidity of the molecular chain, enhances the ability of the polymer molecules to cope with stress fatigue caused by repeated volume changes of silicon-based negative electrode active materials during long cycles, alleviates the volume expansion of the electrode during the charge and discharge process, and improves the cycle stability of the battery; and the polymerization reaction is carried out in the presence of an organic base, through the action of the organic base, while optimizing the bonding performance of the negative electrode active material, the ionic conductivity of the binder is improved, the diffusion rate of lithium ions is increased, which is conducive to deep lithium insertion and improves the rate performance and capacity of the battery.
[0086] In a possible implementation, the preparation method comprises the following steps:
[0087] Step 1: Disperse the first monomer, the second monomer and the organic base in a solvent and stir them evenly to obtain a mixed solution.
[0088] Select a suitable second monomer and an organic base, disperse the two and acrylic acid in a solvent according to a certain mass ratio, and stir evenly to obtain a mixed solution.
[0089] Furthermore, the solvent may be deionized water.
[0090] Furthermore, the mass ratio of the total mass of the first monomer, the second monomer and the organic base to the solvent is 1:(5-20), for example selected from 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20 or a range consisting of any two of them.
[0091] Step 2: In an oxygen-free atmosphere, an initiator is added to the mixed solution to carry out a polymerization reaction, and the binder is obtained after the reaction is completed.
[0092] The mixed solution prepared in step 1 is heated to raise its temperature to a suitable temperature for the corresponding initiator reaction. After the temperature is stabilized, an initiator is added to the mixed solution to carry out a polymerization reaction.
[0093] It should be noted that the polymerization reaction should be carried out in an oxygen-free atmosphere. Before heating the mixed solution, an inert gas should be first injected into the mixed solution to remove oxygen from the mixed solution, and the inert gas should be continuously injected until the polymerization reaction is completed.
[0094] Furthermore, the inert gas is argon.
[0095] In a possible implementation, the initiator may be selected from one or more of an inorganic peroxide initiator, an organic peroxide initiator, a redox initiator or an azo initiator.
[0096] Furthermore, the initiator is an azo initiator, specifically azobisisobutylamidine hydrochloride.
[0097] Furthermore, based on the total mass of the first monomer, the second monomer and the organic base, the mass of the initiator is 0.1 to 0.5%, that is, the mass ratio of the total mass of the first monomer, the second monomer and the organic base to the initiator is 1:(0.001 to 0.005), for example, selected from 1:0.001, 1:0.002, 1:0.003, 1:0.004, 1:0.005 or a range composed of any two of them.
[0098] In a possible implementation, the polymerization reaction can be carried out in a polymerization reactor, the polymerization reaction temperature is controlled to be 40°C to 55°C, the time is 18 to 24 hours, and the polymerization reaction is carried out under stirring at a stirring speed of 300rpm to 500rpm.
[0099] After the reaction is completed, an alkaline substance is added to the reaction product to neutralize the unreacted acrylic acid monomer to obtain the adhesive, which can be specifically carried out according to conventional technical means in the art.
[0100] A third aspect of the present application provides an electrode sheet, which includes any of the above-mentioned binders, or includes a binder prepared by any of the above-mentioned preparation methods.
[0101] Based on the binder provided in the first aspect of the present application or the binder prepared by the preparation method provided in the second aspect, the electrode sheet including the binder also helps to improve the rate performance and capacity of the battery.
[0102] In a possible implementation, the electrode sheet is a negative electrode sheet.
[0103] Furthermore, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector. The negative electrode current collector is generally a metal foil, such as copper foil or carbon-coated copper foil, and the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder. The negative electrode active material includes a silicon-based negative electrode active material (Si, SiOx (0.9<x<1.7), Si / C), a phosphorus-based negative electrode active material (red phosphorus, white phosphorus, black phosphorus) and other alloyed negative electrode materials and a mixture of the above materials. Of course, the negative electrode active material may also include conventional carbon negative electrode active materials such as graphite; the conductive agent may be selected from but not limited to one or more of super-P, conductive carbon black, carbon nanotubes, and acetylene black; the binder is the binder provided in the first aspect of the present application.
[0104] Furthermore, the particle size of the silicon-based negative electrode active material is 10 nm to 100 μm. In addition, according to the needs of those skilled in the art, the silicon-based negative electrode active material is subjected to conventional modification and pretreatment steps such as surface coating and pre-lithiation.
[0105] Furthermore, the mass ratio of the negative electrode active material, the conductive agent and the binder can be determined according to conventional technical means in the art. For example, the mass ratio of the negative electrode active material, the conductive agent and the binder is 8:1:1.
[0106] In one possible implementation, the negative electrode active material layer also includes other auxiliary materials, such as one or more of a cross-linking agent, a dispersant and a surfactant, wherein the cross-linking agent helps to assist in constructing a three-dimensional network system, improve bonding stability, and improve the overall performance of the battery; the dispersant and the surfactant help to improve the dispersibility of the binder.
[0107] Furthermore, the crosslinking agent is selected from one or more of an epoxy crosslinking agent, a silane coupling agent, an aziridine crosslinking agent, and an isocyanate crosslinking agent.
[0108] Furthermore, the dispersant is selected from one or more of sodium carboxymethyl cellulose (CMC), sodium alginate and chitosan.
[0109] Furthermore, the surfactant is selected from one or more of anionic surfactants, nonionic surfactants and cationic surfactants.
[0110] Furthermore, other auxiliary materials at least include a cross-linking agent, and the mass ratio of the binder to the cross-linking agent is 100:1 to 100:5.
[0111] In a possible implementation, the preparation of the negative electrode sheet first requires the preparation of a negative electrode active material layer slurry, which is then coated on the surface of the negative electrode current collector and dried and cut to obtain the negative electrode active material layer slurry. In order to obtain a stably dispersed negative electrode active material layer slurry, the present application provides a method for preparing a negative electrode active material layer slurry, which specifically includes the following steps:
[0112] First, other auxiliary materials are dispersed in a solvent to obtain a first dispersed slurry, wherein the mass of the dispersant is 0.1% to 0.5% of the total mass of the first dispersed slurry, the mass of the cross-linking agent is 0.1% to 0.5% of the total mass of the first dispersed slurry, and the mass of the surfactant is 0.1% to 0.5% of the total mass of the first dispersed slurry.
[0113] Secondly, adding the negative electrode active material and the conductive agent into the first dispersed slurry to prepare a second dispersed slurry;
[0114] Finally, the binder is added into the second dispersed slurry and stirred evenly to obtain a stable and uniform negative electrode active material layer slurry.
[0115] Furthermore, the solvent may be deionized water; and the solid content of the negative electrode active material layer slurry is 25% to 40%.
[0116] A fourth aspect of the present application provides a secondary battery, comprising any one of the electrode sheets described above.
[0117] Based on the characteristics of the electrode sheet provided by the present invention, a battery including the electrode sheet has good cycle performance, rate performance and capacity utilization.
[0118] In a specific embodiment, the battery can be a lithium-ion battery.
[0119] Taking the electrode sheet as a negative electrode sheet as an example, the secondary battery provided in the present application includes, in addition to the negative electrode sheet, a positive electrode sheet, a separator and an electrolyte.
[0120] In a possible implementation, the positive electrode plate includes a positive electrode current collector (generally aluminum foil) and a positive electrode active material layer disposed on the surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder, wherein the positive electrode active material may be selected from but not limited to one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate; the conductive agent may be selected from but not limited to one or more of super-P, conductive carbon black, carbon nanotubes, and acetylene black; the binder may be the binder provided in the first aspect of the present application, or may be a conventional binder in the art, such as PVDF; the solvent may be N-methylpyrrolidone (NMP).
[0121] In a possible implementation, the separator may be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0122] In a possible implementation, the electrolyte is an electrolyte solution, and the electrolyte solution includes at least an organic solvent and a lithium salt.
[0123] Furthermore, the organic solvent can be selected from at least one of ethylene carbonate, butylene carbonate, propylene carbonate, ethyl methyl carbonate, vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, difluoroethylene carbonate, fluorodimethyl carbonate, dimethyl carbonate, diethyl carbonate, and dipropyl carbonate.
[0124] Furthermore, the lithium salt may be selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), and lithium bis(fluorosulfonyl)imide (LiFSI).
[0125] A fifth aspect of the present application provides an electronic device, wherein a driving source or an energy storage source of the electronic device includes the secondary battery described above.
[0126] The electronic device provided in the present application uses the aforementioned secondary battery as a driving source or energy storage unit, so it has excellent battery life and service life.
[0127] The electronic devices may include but are not limited to mobile phones, tablet computers, laptop computers, ultra-mobile personal computers (UMPCs), handheld computers, walkie-talkies, netbooks, POS machines, personal digital assistants (PDAs), wearable devices, virtual reality devices and other mobile or fixed terminals with batteries.
[0128] Hereinafter, the binder and the secondary battery provided in the present application are introduced in detail through specific embodiments.
[0129] Example 1
[0130] The binder provided in this embodiment is obtained by polymerization of acrylic acid and dimethylaminoethyl acrylate in the presence of 1-ethylimidazole, and the preparation method specifically comprises the following steps:
[0131] Step 1: At room temperature, add 17.14 g of acrylic acid, 6.85 g of 1-ethylimidazole, and 6 g of dimethylaminoethyl acrylate into 270 ml of water, stir and dissolve at a speed of 300 rpm to obtain a mixed solution.
[0132] Step 2: Bubble argon to remove oxygen from the mixed solution, and heat the mixed solution to 50° C. in a water bath in an oxygen-free atmosphere. After the temperature stabilizes, add 0.06 g of initiator AIBA (azobisisobutylamidine hydrochloride) and carry out polymerization for 18 hours while maintaining the rotation speed unchanged.
[0133] Step 3: Add 150 ml of ice deionized water to the reaction system to dilute it and place it in an ice water bath to terminate the reaction. Add 6.66 g of sodium hydroxide to neutralize the acrylic acid and continue stirring for one hour before discharging the material to obtain a binder.
[0134] Example 2
[0135] The adhesive provided in this embodiment is obtained by polymerization of acrylic acid and dimethylaminoethyl acrylate in the presence of 1-ethylimidazole.
[0136] The preparation method of the adhesive provided in this embodiment can refer to Example 1, except that the mass of acrylic acid is 14.28 g, the mass of 1-ethylimidazole is 5.72 g, and the mass of dimethylaminoethyl acrylate is 10 g.
[0137] Example 3
[0138] The adhesive provided in this embodiment is obtained by polymerization of acrylic acid and dimethylaminoethyl acrylate in the presence of 1-ethylimidazole.
[0139] The preparation method of the adhesive provided in this embodiment can refer to Example 1, except that the mass of acrylic acid is 14.00 g, the mass of 1-ethylimidazole is 8.5 g, and the mass of dimethylaminoethyl acrylate is 7.5 g.
[0140] Example 4
[0141] The adhesive provided in this embodiment is obtained by polymerization of acrylic acid and dimethylaminoethyl acrylate in the presence of 1-methylpyrrolidine.
[0142] The preparation method of the binder provided in this embodiment can refer to Example 1, except that the organic base is 1-methylpyrrolidine, the mass of acrylic acid is 17.50 g, the mass of 1-methylpyrrolidine is 6.50 g, and the mass of dimethylaminoethyl acrylate is 6 g.
[0143] Example 5
[0144] The adhesive provided in this embodiment is obtained by polymerization of acrylic acid and dimethylaminoethyl acrylate in the presence of 4-dimethylaminopyridine.
[0145] The preparation method of the binder provided in this embodiment can refer to Example 1, except that the organic base is 4-dimethylaminopyridine, the mass of acrylic acid is 16.45 g, the mass of 4-dimethylaminopyridine is 7.55 g, and the mass of dimethylaminoethyl acrylate is 6 g.
[0146] Example 6
[0147] The adhesive provided in this embodiment is obtained by polymerization of acrylic acid and dimethylaminoethyl acrylate in the presence of triethylamine.
[0148] The preparation method of the binder provided in this embodiment can refer to Example 1, except that the organic base is triethylamine, the mass of acrylic acid is 17.00 g, the mass of triethylamine is 7.00 g, and the mass of dimethylaminoethyl acrylate is 6 g.
[0149] Example 7
[0150] The adhesive provided in this embodiment is obtained by polymerization of acrylic acid and dimethylaminoethyl acrylate in the presence of N-methylpiperidine.
[0151] The preparation method of the binder provided in this embodiment can refer to Example 1, except that the organic base is N-methylpiperidine, the mass of acrylic acid is 17.05 g, the mass of N-methylpiperidine is 6.95 g, and the mass of dimethylaminoethyl acrylate is 6 g.
[0152] Comparative Example 1
[0153] The binder provided in this comparative example is a commercially available PAA binder with a Mw of 450,000.
[0154] The weight average molecular weight of the binders provided in Examples 1 to 7 was tested by GPC. The test results are shown in Table 1.
[0155] Table 1 Test results of the adhesives provided in Examples 1 to 7
[0156] Organic base Weight average molecular weight Mw Solid content wt% pH Example 1 1-Ethylimidazole 19000 6.65 9 Example 2 1-Ethylimidazole 16000 6.90 9 Example 3 1-Ethylimidazole 16000 5.88 9 Example 4 1-Methylpyrrolidine 16000 6.86 9 Example 5 4-Dimethylaminopyridine 16000 6.68 9 Example 6 Triethylamine 16000 5.95 9 Example 7 N-Methylpiperidine 16000 7.16 9
[0157] Experimental Example 1-1
[0158] This experimental example provides a battery, which specifically includes the binder provided in Example 1, and the specific preparation method is as follows:
[0159] Step 1, 1.25 g of 2 wt% CMC solution and 2.5 g of water were mixed and stirred to obtain a first dispersed slurry;
[0160] Step 2, adding 0.692 g of silicon oxide powder, 3.985 g of graphite powder, 0.06 g of conductive carbon powder, and 0.625 g of a carbon nanotube solution having a solid content of 0.4% to the dispersed slurry, mixing and stirring to obtain a second dispersed slurry;
[0161] Step 3, adding 3.38 g of the binder solution provided in Example 1 to the second dispersed slurry and stirring again to obtain a negative electrode active material layer slurry;
[0162] Step 4: The negative electrode active material layer slurry obtained in step 3 is uniformly coated on one side of a 11 μm thick double-sided carbon-coated copper foil through the gap of a rod coater, and then placed in a vacuum oven at 100°C for 15 hours to remove the solvent, obtaining a loading of 4 mg / cm 2 (layer density) of dry negative electrode sheet;
[0163] Step 5: Combine the negative electrode with the lithium sheet, electrolyte and separator to make a 2025 button battery.
[0164] Experimental Example 2-1
[0165] The battery provided in this experimental example includes the binder provided in Example 2.
[0166] The preparation method of the battery provided in this embodiment can refer to Experimental Example 1-1, except that the binder used is the binder provided in Example 2.
[0167] Experimental Example 3-1
[0168] The battery provided in this experimental example includes the binder provided in Example 3.
[0169] The preparation method of the battery provided in this embodiment can refer to Experimental Example 1-1, except that the binder used is the binder provided in Example 3.
[0170] Experimental Example 4-1
[0171] The battery provided in this experimental example includes the binder provided in Example 4.
[0172] The preparation method of the battery provided in this embodiment can refer to Experimental Example 1-1, except that the binder used is the binder provided in Example 4.
[0173] Experimental Example 5-1
[0174] The battery provided in this experimental example includes the binder provided in Example 5.
[0175] The preparation method of the battery provided in this embodiment can refer to Experimental Example 1-1, except that the binder used is the binder provided in Example 5.
[0176] Experimental Example 6-1
[0177] The battery provided in this experimental example includes the binder provided in Example 6.
[0178] The preparation method of the battery provided in this embodiment can refer to Experimental Example 1-1, except that the binder used is the binder provided in Example 6.
[0179] Experimental Example 7-1
[0180] The battery provided in this experimental example includes the binder provided in Example 7.
[0181] The preparation method of the battery provided in this embodiment can refer to Experimental Example 1-1, except that the binder used is the binder provided in Example 7.
[0182] Comparative Example 1-1
[0183] The battery provided in this experimental example includes the binder provided in Comparative Example 1.
[0184] The preparation method of the battery provided in this embodiment can refer to Experimental Example 1-1, except that the binder used is the binder provided in Comparative Example 1.
[0185] Test Example 1
[0186] The button cells prepared in Experimental Examples 1-1 to 7-1 and Comparative Example 1-1 were charged and discharged at 30°C at a charge and discharge rate of 0.2C in the voltage range of 0.05V to 2V, and the specific capacity (mAh / g) and coulomb efficiency (%) of the button cells under different cycle numbers were obtained, and the results were plotted. Figure 1 The test results are shown.
[0187] Test Example 2
[0188] The button cells prepared in Experimental Examples 1-1 to 7-1 and Comparative Example 1-1 were subjected to step rate performance tests at 0.05C, 0.1C, 1C, and 2C in the same voltage range, and the specific capacities (mAh / g) at different rates were tested and plotted. Figure 2 The test results are shown.
[0189] according to Figures 1-2 It can be seen that the specific capacity of the button batteries provided by Experimental Examples 1-1 to 7-1 is significantly higher than that of Comparative Example 1-1, and the specific capacity at different rates is also better than that of Comparative Example 1-1, indicating that the binder provided in the present application helps to improve the rate performance and capacity of the battery.
[0190] In summary, the binder provided in the present application has excellent mechanical properties and good toughness. As a negative electrode binder, it can buffer the volume expansion of the negative electrode active material during the cycle. At the same time, it is not easy to break and fall off during multiple cycle volume changes, thereby improving the cycle stability of the material; at the same time, the binder provided in the present application has good ionic conductivity, which can increase the diffusion rate of lithium ions on the surface of the negative electrode active material, so that the introduction of the binder does not affect the rate performance, which is conducive to deep lithium embedding and improving capacity utilization. The binder provided in the present application has good bonding properties and has a large number of bonding sites that bind to the hydroxyl groups on the surface of the negative electrode active material. After in-situ cross-linking with a cross-linking agent, it can effectively limit the breakage and pulverization caused by the volume change of the particles during the cycle. The binder provided in the present application has a simple synthesis process and is environmentally friendly. The prepared negative electrode slurry is evenly dispersed and easy to coat, and can be industrially scaled up for production.
[0191] In the description of the specification of this application, the description of the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0192] In the description of the present application specification, the terms "first", "second", "third", "fourth", etc. (if any) are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example.
[0193] In the description of the present application specification, the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.
[0194] In the description of the present application, the term "plurality" refers to two or more.
[0195] In the description of this application specification, the term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the previous and next associated objects are in an "or" relationship; in a formula, the character " / " indicates that the previous and next associated objects are in a "division" relationship.
[0196] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the embodiments of the present application, rather than to limit them. Although the embodiments of the present application have been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A binder suitable for silicon-based negative electrode active materials, characterized in that: The binder is obtained by polymerizing a first monomer and a second monomer in the presence of an organic base; The first monomer is acrylic acid; The glass transition temperature of the second monomer is not higher than 30°C.
2. The adhesive according to claim 1, characterized in that The content of free carboxyl groups in the binder is not less than 20%.
3. The adhesive according to claim 1, characterized in that The weight average molecular weight of the binder is 10000-5000000Da.
4. The adhesive according to claim 1, characterized in that The second monomer has a general structural formula of CH2CR1R2, wherein R1 is selected from one or two of H and -CH3, and R2 is selected from -COOC n H 2n ,-COOC n H 2n+1 、-CONH2、-CONH(C n H 2n+1 )、-CON(C n H 2n+1 2. -COOC n H 2n N(C n H 2n+1 ),-COOC n H 2n N(C n H 2n+1 )2, one or more, n = 1 ~ 8.
5. The adhesive according to claim 4, characterized in that The second monomer is selected from one or more of methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isooctyl (meth)acrylate, (meth)acrylamide, N,N-dimethylacrylamide, N-methylacrylamide, and dimethylaminoethyl acrylate.
6. The adhesive according to any one of claims 1 to 5, characterized in that: The organic base is selected from one or more of aliphatic amines, aromatic amines, imidazoles, pyridines, pyrroles, piperidines and their derivatives.
7. The adhesive according to claim 6, characterized in that The organic base is selected from one or more of methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, aniline, p-phenylenediamine, m-phenylenediamine, 1-ethylimidazole, 4-dimethylaminopyridine, N-methylpiperidine, and 1-methylpyrrolidine.
8. The adhesive according to any one of claims 1 to 7, characterized in that The mass ratio of the first monomer to the second monomer is 1:(0.3-2).
9. The adhesive according to any one of claims 1 to 8, characterized in that The binder is prepared by the following preparation method: Dispersing the first monomer, the second monomer and the organic base in a solvent and stirring them uniformly to obtain a mixed solution; In an oxygen-free atmosphere, an initiator is added to the mixed solution to carry out a polymerization reaction, and the binder is obtained after the reaction is completed.
10. A method for preparing the adhesive according to any one of claims 1 to 9, characterized in that: The steps include: Dispersing the first monomer, the second monomer and the organic base in a solvent and stirring them uniformly to obtain a mixed solution; In an oxygen-free atmosphere, an initiator is added to the mixed solution to carry out a polymerization reaction, and the binder is obtained after the reaction is completed.
11. The preparation method according to claim 10, characterized in that: The mass ratio of the total mass of the first monomer, the second monomer and the organic base to the solvent is 1:(5-20).
12. The preparation method according to claim 10, characterized in that: The initiator is azobisisobutyramidine hydrochloride; And / or, the mass ratio of the total mass of the first monomer, the second monomer and the organic base to the initiator is 1:(0.001-0.005).
13. The preparation method according to claim 10, characterized in that: The polymerization reaction is carried out at a temperature of 40° C. to 55° C. for 18 to 24 hours. The polymerization reaction is carried out under stirring at a stirring speed of 300 rpm to 500 rpm.
14. An electrode sheet, characterized in that: The electrode sheet comprises the binder according to any one of claims 1 to 9, or comprises the binder prepared by the preparation method according to any one of claims 10 to 13.
15. The electrode sheet according to claim 14, characterized in that: The electrode sheet further includes a cross-linking agent.
16. A secondary battery, characterized in that: The secondary battery comprises the electrode sheet according to any one of claims 14 to 15.
17. An electronic device, characterized in that: The driving source or energy storage source of the electronic device includes the secondary battery according to claim 16.
Citation Information
Patent Citations
Negative electrode, method of preparing the same and rechargeable lithium battery including the same
CN103855402A
Binder for electrochemical cells, paste for electrochemical cells, and method for producing electrode for electrochemical cells
CN105794029A
Cited By
Preparation methods of positive electrode slurry, positive electrode plate, sodium ion battery and additive
CN121331823A